Comparative potato genome editing: Agrobacterium tumefaciens-mediated transformation and protoplasts transfection delivery of CRISPR/Cas9 components directed to StPPO2 gene - Gonzalez, Matías Nicolás (2021)
Delivery of the CRISPR/Cas9 components to the plant cells is a key step in its application as a genome editing tool. Here, we compared Agrobacterium-mediated transformation and protoplast transfection with CRISPR/Cas9 components for potato genome editing. Two sgRNAs were designed to simultaneously direct Cas9 to the StPPO2 gene encoding for a tuber polyphenol oxidase (PPO). A binary vector (CR-PPO) was utilized for either Agrobacterium-mediated transformation or for transient expression in protoplasts, while ribonucleoprotein complexes (RNP-PPO) were additionally assayed in protoplasts. Editing efficiency varied, yielding 9.6%, 18.4% and 31.9% of edited lines from Agrobacterium-mediated transformation, RNP-PPO and CR-PPO transient expression in protoplasts, respectively. Furthermore, only the CR-PPO transient expression resulted in lines edited in all four StPPO2 alleles, observed in 46% of the edited lines and confirmed by tuber PPO activity and enzymatic browning analysis. Lines with on-target DNA insertions were found from all three approaches and characterized by sequencing. The dual-sgRNA strategy resulted in a low incidence of the targeted deletion, likely due to contrasting efficiencies between sgRNAs, that was partially evident in the in silico analysis. Our results demonstrate that gene editing efficiency in potato depends on the CRISPR/Cas9 delivery strategy and provide insights to consider when selecting the appropriate methodology.